Inovasi Pembelajaran Digital LearningApps Kepada Guru UPTD SDN Purwamekar - Srie Mulyani; Achmad Ferdiansyach; Aisyah Nina Wangsa; Anti Damayanti Kosasih; Chairunissa; Dea Aldina Lestari; Dede Ahmad Sugandi (Jurnal Bintang Pendidikan Indonesia, 2023)
Media is one of the tools that can convey learning material so that learning objectives can be achieved properly and provide concrete examples to students. Today's young generation is so close to the name technology, where teachers as much as possible to utilize technology. In learning, teachers can use digital-based learning media, one of which can use the LearningApps website, because learning using digital media can attract children's attention, can facilitate children to be able to learn more widely, more, and varied. The purpose of this service activity, to introduce this LearningApps website to teachers so that it can be implemented in learning activities. This service activity is carried out using the planning and implementation method. When teachers try to use the LearningApps website, there are some difficulties but teachers can solve them well with the help and directions that have been explained. Even though they had difficulties, teachers were still interested in learning to use LearningApps and teachers' skills seemed to have improved in this workshop on the use of digital-based learning media.